INDIKATOR PERANCANGAN OCEANARIUM TANGGAP PANDEMI - Wiraguna, Sidi Ahyar; Lianto, Fermanto (Universitas Tarumanagara, 2021)
According to data compiled by Johns Hopkins University, the COVID-19 virus has spread to all countries and regions of the world, infecting and killing people globally since it first emerged in the Chinese city of Wuhan late last year. The impact of COVID-19 has caused several tourism destinations in Jakarta to be closed. One of the public facilities affected is an oceanarium recreation area which functions as a centre for public entertainment, education and scientific research. The purpose of this study was to obtain design indicators for a pandemic-responsive oceanarium to reduce the risk of spreading and transmitting the COVID-19 virus. This research was conducted using literature studies, interviews, questionnaires and direct observation of similar existing buildings, namely Seaworld Ancol, Jakarta Aquarium and Dunia Fresh Air. The reference theories used that are relevant to the theme of this research include the theory of the spread and transmission of the COVID-19 virus through the air and the HVAC system, the theory of the oceanarium, and other supporting theories. Based on the results of the analysis and discussion, it is concluded that several design indicators can be used as the basis for the concept of a design strategy, namely: 1) The importance of natural air ventilation; 2) HVAC system used; 3) Limiting the duration of visits in a closed room; 3) Design of a separate building mass; 4) Minimizing direct contact between visitors and managers and visitors with visitors; 5) Maintain distance between visitors, visitors and operators. Keywords: HVAC; Design Indicators; Oceanarium; Pandemic Response; Jakarta. AbstrakVirus COVID-19 telah menyebar ke seluruh negara dan wilayah dunia, menginfeksi dan membunuh orang secara global sejak muncul pertama kali di kota Wuhan, China, akhir tahun 2019, menurut data yang dikumpulkan oleh Universitas Johns Hopkins. Dampak COVID-19 menyebabkan sejumlah Destinasi Pariwisata di Jakarta ditutup. Salah satu fasilitas umum yang terdampak adalah tempat tempat rekreasi oceanarium yang berfungsi sebagai pusat hiburan umum, pendidikan dan penelitian ilmiah. Tujuan penelitian ini adalah untuk mendapatkan indikator-indikator desain oceanarium tanggap pandemi sehingga dapat mengurangi resiko penyebaran dan penularan virus COVID-19. Penelitian ini dilakukan dengan metode kombinasi studi pustaka, wawancara, kuesioner dan observasi langsung terhadap bangunan sejenis yang sudah ada yaitu, Seaworld Ancol, Jakarta Aquarium dan Dunia Air Tawar. Beberapa teori acuan yang digunakan yang relevan dengan tema penelitian ini diantaranya adalah, teori penyebaran dan penularan virus COVID-19 melalui udara dan sistem HVAC, teori tentang oceanarium dan teori pendukung terkait lainya. Berdasarkan hasil analisis dan pembahasan diperoleh kesimpulan beberapa indikator perancangan yang dapat digunakan sebagai landasan konsep strategi desain yaitu: 1) Pentingnya ventilasi udara alami; 2) Sistem HVAC yang digunakan; 3) Membatasi durasi kunjungan di dalam ruangan tertutup; 3) Desain masa bangunan yang dipisah-pisah; 4) Meminimalisir kontak langsung antara pengunjung dengan pengelola dan pengunjung dengan pengunjung; 5) Menjaga jarak antara sesama pengunjung, pengunjung dengan operator.